Evaluation of Risk Factors for Antibiotic Resistance in Patients with Nosocomial Infections Caused by Pseudomonas aeruginosa - Meliha Cagla Sonmezer; Gunay Ertem; Fatma Sebnem Erdinc; Esra Kaya Kilic; Necla Tulek; Ali Adiloglu; Cigdem Hatipoglu (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Pseudomonas aeruginosa (P. aeruginosa) is resistant to various antibiotics and can cause serious nosocomial infections with high morbidity and mortality. In this clinical study, we investigated the risk factors in patients who were diagnosed with P. aeruginosa-related nosocomial infection. Methods. A retrospective case control study including patients with P. aeruginosa-related nosocomial infection. Patients who were resistant to any of the six antibiotics (imipenem, meropenem, piperacillin-tazobactam, ciprofloxacin, amikacin, and ceftazidime) constituted the study group. Results. One hundred and twenty isolates were isolated. Various risk factors were detected for each antibiotic in the univariate analysis. In the multivariate analysis, previous cefazolin use was found as an independent risk factor for the development of imipenem resistance (OR = 3.33; CI 95% [1.11–10.0]; p = 0.03), whereas previous cerebrovascular attack (OR = 3.57; CI 95% [1.31–9.76]; p = 0.01) and previous meropenem use (OR = 4.13; CI 95% [1.21–14.07]; p = 0.02) were independent factors for the development of meropenem resistance. For the development of resistance to ciprofloxacin, hospitalization in the neurology intensive care unit (OR = 4.24; CI 95% [1.5–11.98]; p = 0.006) and mechanical ventilator application (OR = 11.7; CI 95% [2.24–61.45]; p = 0.004) were independent risk factors. Conclusion. The meticulous application of contact measures can decrease the rate of nosocomial infections.